Bibliometric Analysis of GIS-based Tourism Research: Trends, Topics, and Future Directions in Terms of Sustainable Tourism Management - Kevser Çınar; Saadet Zafer Kavacık; Emrullah Erul (SAGE Open)
The goal of this study is to evaluate the use of the Geographic Information System (GIS) in tourism research. While there is a lot of research on the various aspects of GIS in tourism, there is currently a lack of a comprehensive overview of the existing studies. This study aims to address this gap by conducting a bibliometric analysis of 434 articles on GIS-based tourism and sustainability research papers that were published between 1996 and 2023 in the Web of Science (WoS) database. The research investigates 434 articles gathered as of January 11, 2024. Bibliometric analysis is conducted using the VOS viewer program. Multiple techniques are applied, including bibliographic coupling of countries and journals, co-authorship analysis among countries, co-citation analysis of journals, and examination of author keywords and abstract term co-occurrences. Moreover, longitudinal trends in publications and citations pertaining to GIS-based tourism and sustainability articles are analyzed in the study. The use of advanced GIS techniques is essential for making informed decisions in sustainable tourism management by better comprehending the factors that influence visitor demand.